8 - NEPAD and the Digital Divide: The Case of Botswana and the Silent Marginalised Minorities: DOI: 10.4314/ad.v30i1.22217 - Mphinyane, Sethunya Tshepho (Africa Development, 2005)
This paper addresses the question of whether the New Partnership for Africa deve lopment (NEPAD) through its e-Africa Commission and its Science and Techno logy agenda for ICT provides for new possibilities for Africa's marginalised indi genous minorities to engage meaningfully with development processes. It questions whether NEPAD recognises the power of ICT beyond providing access to informa tion, particularly its potential as a resource for the oppressed to wage their battles for self-determination, and willing to go beyond questions of access, and address the politics of power and the Internet and other ICT. Is there likelihood in Africa, for ICTs to become new sites of resistance and oppression? The paper suggests that there is already evidence that for marginalised ethnic minorities such as the Basarwa, the San peoples of Botswana, this new forum and the Internet in particular will be yet another tool to mute their voices.